Synthesis of Ferrous Fumarate from Indonesian Iron Sand and In Vivo Body Weight Gain Test in Rats - Rukmana, Taufiq Indra; Kurniadi, Felicia Natalia; Harmita, Harmita (Pharmaceutical Sciences and Research, 2023)
Iron deficiency anemia (IDA) is a health problem in Indonesia. Prevention and treatment of IDA is carried out by giving fortified foods and oral iron therapy. Both can use ferrous fumarate which is made with reacting bivalent iron and disodium fumarate. Bivalent iron can be obtained from iron sand in Indonesia. This study aims to synthesize ferrous fumarate from Indonesian iron sand, which is from Malang, Sukabumi, and Cianjur area, and to determine its absorption through in vivo body weight gain test in male Wistar white rats (Rattus norvegicus). First, ferrous fumarate was synthesized through reaction of ferrous sulfate, which was made from Indonesian iron sand with the highest iron content, which was from Sukabumi area, and disodium fumarate. Second, in vivo body weight gain test was conducted to 3 rat groups (negative control, ferrous sulfate group, and ferrous fumarate group, respectively) and monitored for two weeks. The results showed that ferrous fumarate was successfully obtained as brownish red-orange fine powder with yield of 62.17 ± 1.66 %. In addition, the in vivo body weight test suggested that the rats from ferrous fumarate group showed similar weight gain (35.1%) compared to those from the ferrous sulfate group (30.6%), indicating a possibility of iron absorption from ferrous fumarate.